. Development of Locomotor Basic Motion Learning Through Traditional Games at The Elementary School Level - Perabunita; Lanos, Muhsana El Cintami; Widya Handayani; Hikmah Lestari; Bayu Iswana (Universitas PGRI Palembang, 2025)
This research aims to develop a learning model for basic locomotor movements through a traditional game approach. The study uses a Research and Development (R&D) methodology adapted from the Borg and Gall model, focusing on three stages: (1) Research and Information Collection, (2) Planning, and (3) Initial Product Development. Data were collected using observations, questionnaires, and interviews, analyzed both qualitatively and quantitatively. The needs analysis revealed the need for an innovative and engaging learning model to enhance the learning experience of elementary school students. In the planning phase, a team of experts was formed to design the product. The initial development stage resulted in a learning model integrating traditional games as a medium for basic locomotor movements. Theoretical validation was conducted with experts in learning, material, and media. The outcome is the Bintang Nyago learning model, designed to improve basic locomotor skills through traditional games. The model was validated by experts with material experts rating it 85.83%, learning experts scoring 0.94, and media experts 0.95. The feasibility test showed 90%, practicality test 100%, and effectiveness test 100%, with a significant improvement in students' pre-test (79) and post-test (89) scores. This model proved effective in enhancing students' movement skills, cooperation, confidence, and discipline. The results support the use of modified traditional games to meet the developmental needs of elementary school students.